Viral hepatitis in chicken and turkeys. Issue 2 (15th May 2017) - YOUNUS, M.; NISA, Q.; MUNIR, M.T.; JAMIL, T.; KABOUDI, K.; REHMAN, Z.U.; UMAR, S.; SHAH, M.A.
Abstract : The liver is the 'central laboratory' of a chicken's body, responsible for sorting and transforming digested compounds as well as dealing with waste products. It is essential that this organ is kept in an excellent condition in order to maintain a healthy bird. Viral hepatitis in poultry is a complex disease syndrome caused by several viruses belonging to different families, including fowl adenoviruses (FAdV), avian hepatitis E virus (HEV), duck hepatitis virus (DHV), and turkey hepatitis virus (THV). Although, these viruses target the liver primarily, they each possess unique clinical and biological features. Hydropericardium syndrome (HPS) is a highly infectious disease caused by FAdV serotype 4 (FAdV-4) affecting poultry, especially broilers, and is characterised by the accumulation of fluid in the pericardial sac and hepatitis. Inclusion body hepatitis (IBH) was recognised firstly in the US, and the disease has now been reported in many countries. FAdV, the causative agent of inclusion body hepatitis, is a Group I avian adenovirus in the genus Aviadenovirus. The affected birds have a pale, swollen, friable, and haemorrhagic liver with pathognomonic histological lesions including intranuclear inclusion bodies in the nuclei of the hepatocytes. Avian HEV naturally infects chickens and is associated with hepatitis-splenomegaly syndrome, although the majority of the infected birds are subclinical. THV is a picornavirus that is likely the causative agent of turkey viral hepatitis. Currently there are more questions than answers about THV, and pathogenesis and clinical impact remains largely unknown. Future research into viral hepatic diseases of poultry is warranted to develop effective vaccines, specific diagnostic assays, and identify suitable cell culture systems for virus propagation. This review covers the common and unique features of major hepatitis causing viruses, with emphasis on FAdV, HEV and THV in an effort to identify the knowledge gaps and aid prevention and control of poultry viral hepatitis.